USE OF INDUSTRIAL WASTE IN THE DIET OF DAIRY CATTLE - Chaves, Brunele Weber; Stefanello, Flávia Santi; Burin, Ana Paula; Ritt, Luciano Antonio; Nornberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This review aims at evaluating the use of industrial waste as a nutritional alternative to dairy cattle, in order to combine high production cost reduction which leads to greater gains to producers. This cost reduction may also be linked to an environmental appeal because it is waste generated by industries that are likely to be treated as waste. Some of the waste as the yerba mate industry, the residue from the brewing industry, the winemaking industry waste and citrus pulp are some examples of currently available and which arouse increasing interest of producers, researchers and industries. The residue using yerba mate industry, which carries important and proven antioxidant power emerges as an interesting alternative especially when it comes to the state of Rio Grande do Sul, where the use of yerba mate has a strong relationship with the local culture, despite still little explored for use in animal feed, this alternative comes in an interesting way to dispose the amount of waste generated. The residue from the brewing industry also brings with it the antioxidant potential and proven that can be transferred to animal products, in addition, a part of Brazilian culture and world beer consumption with high consequent generation of waste in the industry. The residue of the wine industry also has the potential addition of antioxidant constituents interesting in terms of fiber and energy and it is important to generate another source of income to wine or fruit juice industry. Citrus pulp has already consolidated its use in animal nutrition, especially when it comes to energy source because it is a waste of juices and other products industry has the differential in reducing acquisition costs. Thus, residues mentioned in this review have their different potentials exploited in order to justify their use in animal nutrition in replacement of conventional foods, both in order to maximize production costs without prejudice productivity and exploring environmental issues so prized currently have recovery of waste by industries generating income and reducing environmental contamination by disposal of these wastes into the environment.